Historical fire frequency (1779-2013) in pine-oak forests in the community of Charcos, Mezquital, Durango - Molina-Pérez, Iván M.; Cerano-Paredes, Julián; Rosales-Mata, Sergio; Villanueva-Díaz, José; Cervantes-Martínez, Rosalinda; Esquivel-Arriaga, Gerardo; Cornejo-Oviedo, Eladio (Revista Chapingo Serie Ciencias Forestales y del Ambiente, 2017)
Historical fire regimes were reconstructed using dendrochronological methods to provide basic information for understanding this phenomenon. In order to reconstruct the fire history in a pine-oak forest in Mezquital, Durango, we collected 78 samples from different fire-scarred tree species (Pinus durangensis, P. arizonica, P. ayacahuite, P. teocote and Pseudotsuga menziesii); 73 and 27 % of the samples were taken from live and dead trees, respectively. By applying dendrochronological methods a total of 75 samples (96 %) and 535 fire scars were dated. Fire regimes were reconstructed from 1746 to 2013, with 1779 being the year of the first recorded fire. A mean fire interval (MFI) of 2.0 years and a Weibull median probability interval (WMPI) of 1.8 years (all scars) were reconstructed. Considering 25 % of scars or more (large fires), a MFI and a WMPI of 7.0 and 5.9 years, respectively, were determined. In total, 92.2 % of fires were categorized as having occurred in the spring and only 7.8 % in the summer. There was no significant (P < 0.05) influence of rainfall and the El Niño Southern Oscillation (ENSO) on fire frequency; however, extensive fires were positively associated with decreased rainfall and ENSO events (La Niña phase).